2017
DOI: 10.1016/j.jtcvs.2016.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Liver health in adults with Fontan circulation: A multicenter cross-sectional study

Abstract: Regardless of modality, findings of liver disease are common among adults with Fontan circulation, even those appearing clinically well. Cirrhosis is present in up to one-third of subjects. Correlations between hepatic fibrosis stage and clinical history or findings on noninvasive testing are few. Further research is needed to identify patients at risk for more severe liver disease and to determine the best methods for assessing liver health in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 38 publications
(55 reference statements)
1
100
2
Order By: Relevance
“…Swartz et al reported 100% sinusoidal and 92% portal based fibrosis in biopsies of only 13 patients. A multicenter study by Wu et al examined 68 biopsies and found 97% with sinusoidal fibrosis and 90% with portal fibrosis . The congestive hepatic fibrosis score (CHS) does not address the clinically relevant range of portal fibrosis between central fibrosis (CHS 2B) and cirrhosis (CHS 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Swartz et al reported 100% sinusoidal and 92% portal based fibrosis in biopsies of only 13 patients. A multicenter study by Wu et al examined 68 biopsies and found 97% with sinusoidal fibrosis and 90% with portal fibrosis . The congestive hepatic fibrosis score (CHS) does not address the clinically relevant range of portal fibrosis between central fibrosis (CHS 2B) and cirrhosis (CHS 4).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, early central fibrosis is not evaluated in traditional scoring systems, such as the Ishak score and METAVIR, which ignore specific characteristic of the Fontan liver. Due to the limitations of applying existing histologic scoring systems to Fontan associated liver disease, most studies examining liver biopsies have relied on reporting multiple scoring systems and even adding fibrosis scores when evaluating Fontan liver fibrosis . These studies highlight the importance of creating a common histologic scoring system for the Fontan population that considers the specific characteristics of the Fontan liver and also the use of noninvasive imaging to evaluate the Fontan liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In addition, abnormal biomarkers of hepatic fibrosis and specimen-proven hepatic fibrosis are common in adults with Fontan circulation. Fontan Associated Liver Disease (FALD).…”
Section: Ac Tive Re S E Arch In Fontan Failure ( Anitha John MD mentioning
confidence: 99%